Biomimetic Fe-bearing nanoparticles in hot spring: morphology, origin and potential bioavailable Fe - Chen, Zhaoying; Liu, Rui; Wang, Yaqin; Lu, Bo; Cui, Yuxiang; Zuo, Lei; Zhang, Peng; Wang, Yaqing; Cao, Cong (Frontiers in Earth Science, 2024)
Iron is a critical redox-active element in geothermal water, and the presence of nanoparticulate Fe is essential in comprehending the intricate cycling of iron and related elements within the natural geothermal ecosystems. In this study, we investigated the mineral properties of Fe-bearing nanoparticles in a hot spring located in Shanxi Province. High-resolution transmission electron microscopy (HRTEM) is utilized for the examination of the morphology, chemical composition, and crystalline structure of Fe-bearing nanoparticles. The findings show that Fe-bearing nanoparticles can exist as single particles measuring 50-200 nm in size, as well as aggregate to form nanoparticle aggregations. The morphology of Fe-bearing nanoparticles mainly includes triangle, axiolitic, and irregular shapes. The selected area electron diffraction patterns reveal the crystal form, amorphous form, and the transition from amorphous to crystalline forms of these nanoparticles. Energy-dispersive X-ray spectroscopy (EDS) analysis indicates that these nanoparticles primarily consist of O and Fe in composition, along with various trace elements including N, Al, Si, Ca, Zn, Cr, Ni, and Mo. These results reveal that goethite and hematite can occur in hot spring. Various in size and modality, tend to cluster into each other, and multiple crystalline states indicate that these iron-bearing nanoparticles are formed through natural processes. In addition, the iron-bearing nanoparticles with biomimetic morphologies (cell-like or microorganism-2 like shapes) may be produced through microbial activity. The biomimetic properties also imply that these nanoparticles may be readily available for biological processes. Significantly, our findings further validate that the shape of iron oxide nanoparticles can serve as an indicator of pH and temperature of the hot spring.